EFFECT OF FORMING PRESSURE ON THE CRITICAL-TEMPERATURE IN YBA2CU3O7-DELTA SUPERCONDUCTORS - (:unkn) unknown (AKADEMIE VERLAG GMBH, 1995)
The effect of pressure on the critical temperature T-c is studied for YBa2Cu3O7-delta compounds prepared under various forming pressures. A systematic decrease in lattice parameters is observed with forming pressure. Resistivity measurements show an increase of the onset temperature T-c0 with forming pressure. A value of dT(c0)/dP approximate to (0.070 +/- 0.010) x 10(-8) K/Pa is determined. A new mechanism based on the variation of the interlayer tunneling integral t(perpendicular to) is used to analyse the experiment results.
Keywords: HIGH-TC SUPERCONDUCTORS; O COMPOUND SYSTEM; TRANSITION-TEMPERATURE; CU-O; HYDROSTATIC-PRESSURE; CARRIER CONCENTRATION; DEPENDENCE; YBA2CU4O8; GPA; LA2CUO4